Tantangan dan Peluang Dakwah Islam di Era Digital - Ardiansyah, Muhammad Rofi; Hamama, Syifa (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2022)
Da'wah in the context of Islam is interpreted as an invitation to goodness. The role of da'wah is important in conveying religious messages in society in a sympathetic and wise manner, and relevant to social and cultural needs. The digital era with the advancement of modern technology offers great opportunities for da'wah. Alternative da'wah media such as social media, allows for the dissemination of religious messages widely and creatively. Media professionals are responsible for creating content that meets ethical and quality standards.